The Factors Affecting the Small and Medium Enterprises Management in Shanghai - Wang, Guangming; Husain, Ahmad Budiman (ALEXANDRIA (Journal of Economics, Business, & Entrepreneurship), 2024)
Administrative aspects are recognized as crucial components for the efficient functioning of the entire enterprise, especially in influencing daily operations. Each administrative link influences regular operations in different ways. At the level of decision-making, the scientific implementation of command and control is highly urgent. The optimum performance of corporate departments relies heavily on the implementation of effective decision-making processes. Although prominent leaders and principals hold significant guiding power over each department, this authority is often misunderstood. The power of leadership should not be overexerted or left unused. Instead, it should be strategically employed to foster and enhance the efficiency and productivity of each department. This study investigates the lasting impact of administrative factors on the efficiency of enterprise management. By promoting efficient administrative practices and well-informed decision-making, leaders can ensure that each department operates at its highest potential. This approach not only streamlines the enterprise's daily operations but also contributes to its long-term success and sustainability. Overall, the study highlights the intricate and essential relationship between administrative factors and enterprise management efficiency.